Construction of dye-sensitized solar cells using wet chemical route synthesized MoSe2 counter electrode - Vikraman, Dhanasekaran; Patil, Supriya A.; Hussain, Sajjad; Mengal, Naveed; Jeong, Sung Hoon; Jung, Jongwan; Park, Hui Joon; Kim, Hak-Sung; Kim, Hyun-Seok (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] •Wet chemical methodology was used to synthesize MoSe2 as a CE for DSSCs.•High PCE of 7.28% achieves using MoSe2 CE, equivalent to Pt CE (7.40%).•Uniform morphology with active sites promotes electrocatalytic activity. This paper presents a simple and large area wet chemical preparation route for molybdenum diselenide (MoSe2) atomic layers. MoSe2 was synthesized onto fluorine doped tin oxide substrates and could be directly used as a counter electrode (CE) for dye-sensitized solar cells (DSSCs). The role of deposition time on the growth of MoSe2 CE was elaborately discussed using Raman, X-ray diffraction and photoluminescence studies. Influence of wet chemical growth time on the surface modification of MoSe2 CE was evidently demonstrated by scanning electron microscopy and atomic force microscopy studies. The MoSe2 CE electrode has lower charge transfer resistance and superior electrocatalytic activity towards triiodide/iodide redox behavior, comparable to conventional Pt CEs. High power conversion efficiency of 7.28% was achieved, equivalent to scarce noble metal Pt CE (7.40%). Uniform surface morphology with active edge sites highly dominated to promote the superior electrocatalytic activity. This work opens a way to use an economical wet chemical method to fabricate the layered MoSe2 CE as a replacement for high cost Pt based CE for DSSCs.